2022
DOI: 10.1021/acsestwater.2c00126
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Partial Nitrification Combined with Nitrite-Denitrification Phosphorus Removal and Simultaneous Nitrification–Endogenous Denitrification for Synchronous Chemical Oxygen Demand, Nitrogen, and Phosphorus Removal

Abstract: A combination of partial nitrification and nitrite-denitrifying phosphorus removal and simultaneous nitrification-endogenous denitrification (nDNPR-SNED) in two sequencing batch reactors was developed for synchronous chemical oxygen demand (COD), nitrogen (N), and phosphorus (P) removal by regulating dissolved oxygen (DO) and influent nitrite concentrations. COD, total nitrogen, and P removal efficiencies of 87.4 ± 0.5, 91.6 ± 1.1, and 97.8 ± 0.6% were obtained after 112 days of anaerobic/anoxic/aerobic operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…4b). C10-SB1A is considered a DNRA bacteria, 31 and its relative abundance first increased and then decreased with the increase in Mn 2+ concentration, and reached the maximum in the group with 10 mM Mn 2+ treatment. The phenomenon revealed that the DNRA in the system was first enhanced and then weakened.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4b). C10-SB1A is considered a DNRA bacteria, 31 and its relative abundance first increased and then decreased with the increase in Mn 2+ concentration, and reached the maximum in the group with 10 mM Mn 2+ treatment. The phenomenon revealed that the DNRA in the system was first enhanced and then weakened.…”
Section: Resultsmentioning
confidence: 99%
“…GAOs are functional bacteria in the process of endogenous denitrication of treated municipal wastewater, which can convert NO 3 − -N and NO 2 − -N to N 2 . 31 As the Mn 2+ concentration increased, the relative abundance of Candidatus_Competibacter gradually decreased, and endogenous denitrication weakened. Ellin6067 is an ammoniaoxidizing bacteria (AOB), which oxidizes ammonia to nitrite.…”
Section: Structural Composition Of Microbial Communitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…With regard to nitrogen metabolism, Tetrasphaera-MAGs lacked the complete denitrification pathway, despite most MAGs encoding enzymes for nitrate reduction. Genes encoding enzymes for nitrite, nitric oxide, and nitrous oxide reduction were sparse …”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding enzymes for nitrite, nitric oxide, and nitrous oxide reduction were sparse. 46 3.3. Phosphorus Release and Uptake by the Community with Different Carbon Sources.…”
Section: Resultsmentioning
confidence: 99%